2023
DOI: 10.18203/2349-3291.ijcp20230090
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Nikshay Poshan Yojna in tuberculosis patients in two tuberculosis units of North India

Abstract: Background: Nikshay Poshan Yojana (NPY) was launched in 2018 aiming to provide nutritional incentive of INR 500 per month to all tuberculosis (TB) patients till they complete their treatment. Aim of present study is to determine the number (proportion) of patients being treated for tuberculosis who received the benefits of NPY and to explore the ways incentives were utilized by the patients. Methods: This cross-sectional study was conducted in two tuberculosis units of North India from June 2022 to Dec 2022. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…Though received late, 88.8% of the PwTB reported fully utilising the NPY benefit for their nutrition. Similar to our results, earlier studies reported, 76% [ 34 ] and 64% [ 24 ] of the PwTB had utilised the benefits for their nutritional requirements. The possible reasons for the remaining 10.2% of PwTB not using the benefit for nutritional requirements could be the delay in receipt, lack of awareness about the purpose of the NPY benefit, and prioritising other household needs over their nutrition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Though received late, 88.8% of the PwTB reported fully utilising the NPY benefit for their nutrition. Similar to our results, earlier studies reported, 76% [ 34 ] and 64% [ 24 ] of the PwTB had utilised the benefits for their nutritional requirements. The possible reasons for the remaining 10.2% of PwTB not using the benefit for nutritional requirements could be the delay in receipt, lack of awareness about the purpose of the NPY benefit, and prioritising other household needs over their nutrition.…”
Section: Discussionsupporting
confidence: 92%
“…Earlier studies have also reported that PwTB who had not received the instalment were more likely to experience unfavourable treatment outcome such as loss of follow-up and death during treatment [ 15 , 39 ]. Timely receipt of instalment enables the PwTB to procure additional nutrition [ 24 ] in the form of protein-rich foods, supplements which improve tolerance to medication [ 40 ] and reduce loss to follow-up [ 15 ]. The better nutrition boosts immunity, also influences the pharmacodynamics and pharmacokinetics of the anti-TB drugs improving bacteriological clearance [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation